Doped sulfide solid electrolyte as well as preparation method and application thereof

By doping soft acid element oxides into sulfide solid electrolytes and adopting a specific preparation method, the problems of air stability and oxidation stability of sulfide solid electrolytes are solved, and higher structural stability and ionic conductivity are achieved, making it suitable for the application of all-solid-state batteries.

CN120698798AActive Publication Date: 2025-09-26SVOLT ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202511195307.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-26
Publication Date
2025-09-26
Estimated Expiration
2045-08-26

AI Technical Summary

Technical Problem

Existing sulfide solid electrolytes have shortcomings in air stability, oxidation stability and structural stability during long-term cycling, which affects their large-scale application in all-solid-state batteries.

Method used

By doping specific soft acid element oxides, such as oxides of Be, Mg, Ca, Sr, Ba, Zn, Pd, Yb or No, into the sulfide solid electrolyte, AS covalent bonds with higher polarity than PS are formed, combined with the fully filled electron layer structure of the soft acid elements, the oxidation resistance and air stability are improved, and the crystal structure is optimized through the preparation methods of microwave plasma pretreatment, mechanical chemical vapor deposition and in-situ densification hot pressing sintering.

Benefits of technology

It significantly improves the air stability and antioxidant capacity of sulfide solid electrolytes, reduces lattice distortion, lowers interface impedance, improves ionic conductivity, enhances long-term cycle stability, and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and provides a doped sulfide solid electrolyte and a preparation method and application thereof, the doped sulfide solid electrolyte comprises an oxide containing a metal element A as a dopant; the atomic valence electron layer of A is fully filled with soft acid elements; in the doped sulfide solid electrolyte, the valence state of A does not exceed + 3. By doping the oxide of specific A, the soft acid element A is more easily and preferentially combined with the soft alkali S < 2-> to replace P and form an A-S covalent bond with polarity higher than that of P-S, so that the air stability of the sulfide solid electrolyte is improved, and the hydrolysis of the sulfide electrolyte is effectively inhibited; meanwhile, the specific electron arrangement structure of the metal element A is fully filled with a valence electron layer, the stability is high, and the oxidation resistance of the sulfide solid electrolyte can be effectively improved. And A is in a relatively low valence state in the doped sulfide solid electrolyte, so that the influence of a high-valence metal doped element is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials and relates to a doped sulfide solid electrolyte and a preparation method and application thereof. Background Art

[0002] With the profound adjustments to the global energy structure and the rapid development of new energy vehicles, energy storage systems, and other fields, the safety risks associated with the use of organic flammable electrolytes in traditional lithium-ion batteries have become increasingly prominent. Against the backdrop of growing demand for higher energy density, safety risks such as thermal runaway, short circuits, and electrolyte leakage have become a bottleneck restricting their further development. Against this backdrop, all-solid-state batteries, which fundamentally eliminate flammability and volatility hazards by replacing liquid electrolytes with solid-state electrolytes, are considered a key development direction for the next generation of high-safety, high-energy-density energy storage.

[0003] The core components of all-solid-state batteries include positive electrode materials, solid electrolytes, and negative electrode materials. Among them, the solid electrolyte, as the key medium connecting the positive and negative electrodes, largely determines the overall performance of the battery, especially key indicators such as ion conductivity, interface stability, cycle life and safety. Compared with traditional liquid electrolytes, solid electrolytes not only need to have good ion transport capabilities, but also need to have excellent chemical stability and mechanical strength to adapt to complex electrochemical environments and effectively inhibit the growth of lithium dendrites. At present, the more widely studied solid electrolytes mainly include three categories: oxide type, polymer type and sulfide type. Among them, sulfide solid electrolytes are popular due to their extremely high lithium ion conductivity (usually up to 10 -2 ~10 -3 S / cm, which is close to or even exceeds that of liquid electrolytes) and has attracted much attention, becoming one of the important candidate materials for realizing high-performance all-solid-state batteries.

[0004] Sulfide solid electrolytes include argyrodite type (such as Li6PS5Cl), LGPS type (such as Li 10 GeP2S 12 ), Thio-LISICON type (such as Li2S-GeS2-P2S5 system) or glassy state (ceramic state), etc. In these materials, due to S 2-Ions have a large ionic radius and low lattice energy, which enables lithium ions to migrate quickly in their crystal structure, thereby exhibiting excellent ionic conductivity. In addition, sulfide solid electrolytes also have relatively low hardness and high ductility, which makes it easier for them to form close physical contact with the positive electrode particles during the pressing process, helping to reduce interfacial voids and improve overall density. At the same time, its ionic conductivity attenuation at low temperatures is small, so it is also considered to be an ideal electrolyte material for working in low-temperature environments. In practical applications, sulfide solid electrolytes can also be used as positive electrode binders or filler phases to replace traditional PVDF / carbon additive combinations, thus having the potential to achieve "full solid-state" positive electrode materials.

[0005] However, although sulfide solid electrolytes show significant advantages in ionic conductivity, they still have many shortcomings in air stability, oxidation stability, and structural stability during long-term cycling, which seriously limit their large-scale application in all-solid-state batteries.

[0006] First, sulfide solid electrolytes generally have poor air stability. In humid air, the hard acid centers in sulfides (such as P 5+ ) easily reacts with hard bases (such as O 2- ) combines to form PO bonds, or weak acid centers S 2- Ions easily react with H + Combining with the electrolyte, H2S gas is generated. This reaction mechanism not only destroys the electrolyte structure but also releases harmful gases, affecting the safety of the production environment. Therefore, the synthesis, processing, and subsequent battery assembly of sulfide solid electrolytes must usually be carried out under a strict dry inert atmosphere, greatly increasing the process complexity and manufacturing cost.

[0007] Second, the oxidation stability of sulfide solid electrolytes is poor, among which S 2- The oxidation potential of sulfide electrolytes is typically between 2.0 and 2.5 V, which is much lower than the operating voltage range of many high-voltage cathode materials (for example, high-nickel ternary materials can have an operating voltage of over 4.3 V). This means that when sulfide electrolytes come into contact with cathode materials, especially high-voltage cathode materials, irreversible oxidation reactions may occur, leading to electrolyte decomposition and the formation of high-impedance interfacial products, which in turn hinder the transport of lithium ions.

[0008] This is also reflected in the problem that when the sulfide solid electrolyte is in direct contact with the oxide positive electrode material, a significant chemical potential difference will be generated between the two. + It will migrate from the electrolyte side to the cathode material until it reaches equilibrium. At this point, Li +The defect layer, i.e., the space charge layer, grows at the beginning of battery charging, which will eventually lead to a large interfacial resistance and delay the Li + Transport at the interface.

[0009] Third, although the low hardness of the sulfide solid electrolyte is conducive to forming good physical contact with the positive electrode material during the pressing process, its high brittleness makes it difficult to prepare a uniform thin film over a large area. During the wet coating process, if a slurry containing a polar solvent is used, the sulfide electrolyte may react with the solvent, producing impurities or releasing H2S gas, affecting the quality and purity of the electrolyte membrane. In addition, during long-term cycling, due to the weak mechanical properties of the material itself, it is easy to crack under the repeated charge and discharge stress, and even be penetrated by lithium dendrites, causing serious internal short circuit risks.

[0010] To address these issues, an effective modification strategy is to introduce a layer of air-stable coating materials, such as Li2CO3 and LiF, onto the surface of the sulfide solid electrolyte. This physically isolates the sulfide from direct contact between moisture and oxygen, thereby mitigating its degradation. However, controlling the thickness of the coating layer is difficult; excessively thick coatings can affect lithium ion transport pathways and reduce the electrolyte's ionic conductivity. Furthermore, the coating layer has limited bonding strength with the sulfide matrix, potentially leading to delamination after multiple cycles or under high-pressure conditions, resulting in a loss of protective effect.

[0011] Another effective modification method is to optimize the crystal structure and chemical stability of sulfide solid electrolytes by element doping. Compared with the coating method, element doping tends to start from the intrinsic level of the material and regulate its electronic structure and chemical bonding characteristics by introducing specific cations or anions. Currently, commonly used doping elements include high-valent metal cations, such as Al 3+ 、Ga 3+ 、Zr 4+ 、Ti 4+ or Sn 4+ These high-valent cations can partially replace the low-valent sites in the sulfide structure (such as Li + ), thereby reducing the concentration of lithium vacancies and inhibiting the adsorption and reaction to H2O / O2. In addition, the MS bond formed by high-valent cations and sulfur is usually stronger than the Li-S bond, which helps to enhance the structural stability of the material and delay the oxidation reaction of sulfur. For example, Zr 4+ Doped Li 10 GeP2S 12 The material showed higher air stability and better oxidation resistance.

[0012] However, the choice of element doping is not indiscriminate, especially the introduction of unstable high-valent cations may have a negative impact on the performance of the electrolyte. High-valent doping elements with poor chemical stability or instability within the electrochemical window will not only destroy the original lithium ion transmission channel, but also further migrate to the interface, thereby hindering ion transmission and causing a significant decrease in ionic conductivity (such as excessive Al 3+ Doping will reduce Li 10 GeP2S 12 Conductivity), it can also cause local lattice distortion, or trigger other side reactions (such as H2S or Li3PO4), and may consume active lithium, thereby accelerating the decay of battery capacity. For example, some mechanisms include: 1) Some high-valent cations may be reduced to low-valent states at low potentials (such as for lithium metal anodes), such as Sn 4+ May be reduced to Sn 2+ / Sn 0 , Ge 4+ May be reduced to Ge 2+ / Ge 0 This process will destroy the lattice integrity of the electrolyte; and the reduction product Sn 0 When nanoparticles segregate at the grain boundaries, they form an electron percolation network, which exacerbates the self-discharge phenomenon and affects the long-term stability of the battery. At the same time, the reduction process is also accompanied by S 2- oxidation reaction, releasing H2S gas or forming Li2S insulating layer, increasing interface impedance; 2) some high-valent elements migrate at the interface and participate in side reactions, such as Ta 5+ Reacts with lithium metal in the interface region to generate high-resistance Li x TaO y compounds, which significantly consume active lithium and form a high-resistance interface layer; 3) at high voltages (>4V vs.Li + / Li) conditions, some high-valent elements (such as Nb 5+ 、Ta 5+ 4) The ionic radius of these high-valent ions used for doping often does not match that of the matrix, resulting in local stress concentration, which is more likely to induce the formation of cracks or pores and promote the growth and penetration of lithium dendrites; 5) The introduction of certain high-valent elements may also reduce the thermal stability of sulfide solid electrolytes, such as in Li7P3S 11 Ta-doped 5+ After that, its decomposition temperature dropped from the original 300℃ to about 250℃, which brought new problems to its application under high temperature conditions.

[0013] In summary, there is still a need to develop a new modification and optimization scheme for sulfide solid electrolytes, which can significantly improve their air stability, antioxidant ability and structural stability during long-term cycles without affecting their intrinsic high ionic conductivity, so as to meet the needs of their large-scale application in the construction of all-solid-state batteries. Summary of the Invention

[0014] In view of the problems existing in the prior art, the present invention aims to provide a doped sulfide solid electrolyte and its preparation method and use, wherein the doped sulfide solid electrolyte comprises an oxide containing a metal element A as a dopant; the atomic valence electron layer of A is fully filled and is a soft acid element; in the doped sulfide solid electrolyte, the valence state of A does not exceed +3. By doping with a specific oxide of A, the soft acid element A is more easily reacted with the soft base S 2- It preferentially binds to replace P, forming an AS covalent bond with a higher polarity than PS, thereby improving the air stability of the sulfide solid electrolyte and effectively inhibiting its hydrolysis. Furthermore, the specific electronic configuration of the metal element A fully fills the valence electron layer, providing strong stability and effectively improving the antioxidant capacity of the sulfide solid electrolyte. Furthermore, A exhibits a lower valence state in the doped sulfide solid electrolyte, avoiding the effects of high-valence metal doping elements.

[0015] To achieve this object, the present invention adopts the following technical solutions:

[0016] In a first aspect, the present invention provides a doped sulfide solid electrolyte, comprising a sulfide solid electrolyte basic component, wherein the sulfide solid electrolyte basic component contains a dopant, and the dopant includes an oxide of a metal element A; the atomic valence electron layer of the metal element A is fully filled, and A is a soft acid element; in the doped sulfide solid electrolyte, the valence state of A does not exceed +3.

[0017] In the doped sulfide solid electrolyte of the present invention, the oxide of the metal element A is used as the doping component. The specific metal element A is a soft acid element. According to the HSAB theory, the soft acid preferentially reacts with the soft base S. 2- Therefore, A can replace P in the basic components of the sulfide solid electrolyte, forming a covalent bond of AS with a higher polarity than PS, which has the ability to inhibit the hydrolysis of the electrolyte; at the same time, the orbital in the atomic valence electron layer of element A is fully filled with electrons, which is more stable and can improve the antioxidant capacity of the sulfide solid electrolyte. Specifically, when the valence electron layer of the atom is fully filled (such as the valence electron layer of Yb is 4f 14The electronic configuration of 6s² is extremely stable, similar to that of noble gases (such as He, Ne, Ar, etc.). The energy of this state is the lowest, and it requires extremely high energy to further lose or accept electrons; to break the fully occupied electron shell (such as removing an electron), a very high ionization energy needs to be overcome, so it is not easily taken away by oxidants (such as O2, H + 、high-valent metal ions, etc.). When applied to sulfide solid electrolytes, the band gap between the fully occupied valence band and the empty conduction band is relatively large, and electrons are difficult to transition, so it is not easily involved in redox reactions. When the doped elements in the sulfide solid electrolyte are more stable, the antioxidant and air stability of the electrolyte are higher. The reason is that the highly stable doped elements have good matching with the matrix, can reduce lattice distortion, lower the sulfur vacancy concentration, and are beneficial to stabilizing the lattice structure and reducing defect activity; the highly stable doped elements form strong bonds in the sulfide lattice, can preferentially occupy the sites vulnerable to oxygen attack (such as sulfur vacancy V s 2- ), prevent oxygen (O2 / H2O) from penetrating into the electrolyte interior, and inhibit sulfur oxidation and H2S release; the highly stable doped elements can reduce the valence state fluctuation of sulfur (avoiding S 2- →S 0 / S 4+ ), thus inhibiting side reactions.

[0018] The following are the preferred technical solutions of the present invention, but not limitations to the technical solutions provided by the present invention. Through the following technical solutions, the technical purposes and beneficial effects of the present invention can be better achieved and realized.

[0019] As a preferred technical solution of the present invention, the basic components of the sulfide solid electrolyte include at least one of Thio-LISICON series electrolytes, Argyrodite series electrolytes or glass-ceramic electrolytes. Preferably, it contains S element and P element.

[0020] Preferably, the chemical formula of the Thio-LISICON series electrolyte includes Li 4-x M 1-x P x S4, (M = at least one of Si, Ge or Sn), 0 < x < 1; for example, Li 3.25 Ge 0.25 P 0.75 S4, etc.

[0021] Preferably, the chemical formula of the Argyrodite series electrolyte includes Li 7-a P a S 6-b X b , X = at least one of F, Cl, or Br, 0 ≤ a ≤ 1, 0 < b ≤ 2; for example, Li6PS5Cl, etc.

[0022] Preferably, the metal element A includes at least one of Be, Mg, Ca, Sr, Ba, Zn, Pd, Yb or No.

[0023] Preferably, the oxide of the metal element A includes at least one of BeO, MgO, CaO, SrO, BaO, ZnO, PdO, Yb2O3 or No2O3.

[0024] Preferably, the ratio of the molar amount of the metal element A to the molar amount of the basic component of the sulfide solid electrolyte is (0.01~0.2):1, for example, it can be 0.01:1, 0.02:1, 0.03:1, 0.05:1, 0.06:1, 0.08:1, 0.1:1, 0.12:1, 0.14:1, 0.16:1, 0.18:1 or 0.2:1, etc.

[0025] Preferably, the chemical structure of the doped sulfide solid electrolyte includes Li a P b S c A e X d O f , wherein X includes at least one of Cl, I, Br or F; a=2.5~12, for example, a can be 2.5, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, etc.; b=0.5~2.5, for example, b can be 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.3c=4~15, d=0.5~3.5, e=0.0067~0.2, f=0.01~0.3, and e:f=1:(1~1.5).

[0026] Preferably, f=e or 2f=3e.

[0027] Preferably, the D of the doped sulfide solid electrolyte 50 The particle size is ≤15μm, for example, it can be 15μm, 14μm, 12μm, 10μm, 9μm, 8μm, 7μm, 6μm, 5μm, 4μm, 3μm, 2μm, 1μm, 0.8μm, 0.5μm, 0.6μm, 0.2μm, 0.1μm, 0.08μm, 0.05μm, 0.03μm or 0.01μm, etc.

[0028] In a second aspect, the present invention provides a method for preparing the doped sulfide solid electrolyte according to the first aspect, the preparation method comprising:

[0029] The sulfide solid electrolyte basic component raw material and the dopant raw material are mixed, and subjected to microwave plasma pretreatment to generate a reduction reaction to obtain a pretreated material;

[0030] Grinding the pretreated material to generate a mechanical chemical vapor deposition synergistic reaction to generate nanocrystals to obtain a grinding material;

[0031] The ground material is subjected to in-situ densification and hot pressing sintering to obtain the doped sulfide solid electrolyte.

[0032] In the preparation method described in the present invention, the raw materials are pretreated with microwave plasma in advance. The surface oxides of the raw materials can be reduced by plasma (such as hydrogen plasma). The microwave energy simultaneously causes lattice defects in the raw materials, thereby enhancing the subsequent reaction activity. Then, a mechanochemical vapor deposition synergistic reaction occurs during the grinding process to promote the synthesis of nanocrystals. Finally, in-situ densification hot pressing sintering is adopted to simultaneously achieve powder forming, sintering and densification, thereby simplifying the process flow.

[0033] It should be noted that the size of the nanocrystals described in the present invention is in the range of 1 to 100 nm, their lattice arrangement is regular, and the structure is short-range ordered, but there may be surface defects or strain; there are a large number of grain boundaries between the nanocrystals, and the grain boundaries are rich, which can affect ion / electron transport.

[0034] As a preferred technical solution of the present invention, the dopant raw material includes an oxide of metal element A.

[0035] As a preferred technical solution of the present invention, the microwave plasma pretreatment is carried out in a mixed plasma atmosphere of an inert atmosphere.

[0036] Preferably, the inert atmosphere includes Ar (argon).

[0037] Preferably, the power range of the microwave plasma pretreatment is 100~300W, for example, 100W, 150W, 200W, 250W or 300W; the vacuum degree is 0.01~0.1Pa, for example, 0.01Pa, 0.02Pa, 0.04Pa, 0.06Pa, 0.08Pa or 0.1Pa, etc.; the temperature is 20~65°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or 65°C, etc.; and the time is 5~20min, for example, 5min, 10min, 15min or 20min, etc.

[0038] Preferably, the flow rate of the inert atmosphere is 20-50 sccm, for example, 20 sccm, 23 sccm, 25 sccm, 28 sccm, 30 sccm, 33 sccm, 35 sccm, 38 sccm, 40 sccm, 42 sccm, 45 sccm, 48 sccm or 50 sccm, etc., to maintain a stable plasma and avoid excessive sputtering; the vacuum degree of 0.01-0.1 Pa is conducive to ensuring plasma uniformity; the power range is 100-300 W, and excessive power can easily lead to sulfur volatilization or lattice damage; the processing time is 5-20 min, and the temperature is 20-65° C. to prevent thermal decomposition of the raw materials.

[0039] As a preferred technical solution of the present invention, the grinding includes at least one of ball milling, high-energy vibration milling, air flow milling, ultrasonic-assisted grinding or cryo-grinding; preferably ball milling.

[0040] The ball milling is carried out in a zirconia ball milling jar, the inner wall of which is plated with a diamond-like carbon coating.

[0041] Preferably, the ball mill has a rotation speed of 400-700 rpm, for example, 400 rpm, 430 rpm, 450 rpm, 480 rpm, 500 rpm, 520 rpm, 550 rpm, 580 rpm, 600 rpm, 620 rpm, 640 rpm, 660 rpm, 680 rpm or 700 rpm, etc.; and a pulse frequency conversion mode is adopted, with a start-stop ratio of 10:(5-2), for example, 10:5, 10:4, 10:3 or 10:2, etc.

[0042] In the present invention, a specially made zirconia ball mill with a diamond-like carbon coating on the inner wall is used to prevent metal (such as iron) contamination from scraping tools during the experiment, and the pulsed frequency conversion mode can further promote the crystallization of nanocrystals.

[0043] Preferably, the ball milling time is 30 min to 12 h, for example, 30 min, 40 min, 50 min, 60 min, 1.2 h, 1.5 h, 1.8 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h.

[0044] As a preferred technical solution of the present invention, the temperature and pressure of the in-situ densification hot pressing sintering are increased step by step.

[0045] Preferably, the temperature range of the in-situ densification hot pressing sintering is 50-500°C, such as 50°C, 80°C, 100°C, 130°C, 150°C, 180°C, 200°C, 230°C, 250°C, 280°C, 300°C, 330°C, 350°C, 380°C, 400°C, 420°C, 450°C, 480°C or 500°C; the pressure range is 5-300MPa, such as 5MPa, 8MPa, 10MPa, 30MPa, Pa, 50MPa, 80MPa, 100MPa, 130MPa, 150MPa, 180MPa, 200MPa, 230MPa, 250MPa, 280MPa or 300MPa, etc.; the processing time of each stage is 30min~12h, for example, 30min, 45min, 60min (1h), 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, etc.

[0046] In this invention, the in-situ densification hot-pressing method achieves densification at a lower temperature (50-100°C lower than pressureless sintering), effectively reducing interfacial side reactions between the solid electrolyte and the positive electrode during subsequent application. Increasing the applied pressure while heating (typically 200-400°C) promotes plastic deformation and diffusion of the particles, ultimately achieving a relative density exceeding 95% (close to the theoretical density). The doped sulfide solid electrolyte achieved through in-situ densification hot-pressing achieves close grain boundary contact, significantly reducing grain boundary resistance and improving ionic conductivity.

[0047] Specifically, the densification method of normal pressure and high temperature sintering (such as 900°C) in the existing technology is prone to cause lithium volatilization (such as Li2O and Li2S gasification), causing the electrolyte stoichiometric ratio to deviate (such as the reduction of Li-rich phase), and lithium depletion-type side reactions are prone to occur when in contact with the positive electrode (such as NCM) (such as the generation of high-impedance Li2CO3 at the interface).

[0048] The hot-pressing and low-temperature sintering in the present invention reduces temperature dependence through pressure-assisted densification, inhibits high-temperature-induced interfacial instability, reduces lithium volatilization and loss, and component segregation, and maintains electrolyte chemical uniformity. Secondly, high-temperature, normal-pressure sintering easily causes the melting or aggregation of impurities (such as sintering aid Li3BO3 or residual Li2CO3) at grain boundaries. These impurities will react with the positive electrode during battery cycling (such as generating Li2O or CO2). The low temperature and high-pressure stress of the hot pressing in the present invention can inhibit impurity phase migration and promote the formation of pure grain boundaries. Therefore, the present invention can optimize the microstructure, reduce interface defects, reduce open pores inside the electrolyte, avoid local side reactions caused by the embedding of positive electrode active materials (such as Ni-rich NCM) in the pores, reduce interfacial contact resistance, and inhibit lithium dendrite growth caused by uneven current distribution. It is also beneficial to uniform grain size, avoiding cracks caused by stress concentration at large grain boundaries and the resulting accelerated degradation of the positive electrode / electrolyte interface.

[0049] Preferably, the preparation method further comprises crushing the obtained doped sulfide solid electrolyte to achieve a target particle size.

[0050] In a third aspect, the present invention provides a positive electrode sheet, wherein the positive electrode sheet contains the doped sulfide solid electrolyte described in the first aspect.

[0051] Preferably, the positive electrode active material in the positive electrode active layer of the positive electrode sheet is pre-lithiated to form a lithium-rich layer on the surface.

[0052] Preferably, the lithium-rich layer includes a lithium source, and the lithium source includes at least one of Li2CO3, Li3N, Li2O, Li2TiO3, Li3PO4, AlF6Li3, AlHLiO2, AlCl4Li or Li2O3Ti.

[0053] Preferably, the method for forming the lithium-rich layer includes: mixing the positive electrode active material and the lithium source, grinding, and calcining; the grinding speed is 300-500 rpm, and the time is 0.5-2 hours; the calcination temperature is 400-500°C, and the time is 1-3 hours.

[0054] Preferably, the mass of the lithium-rich layer accounts for 0.1% to 1% of the mass of the positive electrode active material, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.

[0055] It should be noted that the application of the doped sulfide solid electrolyte described in the present invention in batteries includes the following methods: directly mixing the doped sulfide solid electrolyte into the active layer of the positive electrode sheet, and performing mixing, slurrying, coating, rolling and other processes together with other raw materials in the positive electrode active layer. Due to the presence of a space charge layer between the sulfide solid electrolyte and the positive electrode active material (oxide positive electrode), the transmission of lithium ions at the positive electrode / electrolyte interface is hindered, resulting in high interfacial impedance and polarization. Therefore, further, the present invention can use other lithium sources to pre-lithiate the positive electrode active material to form a lithium-rich layer, obtain the pre-lithiated positive electrode active material, and then mix it with the doped sulfide solid electrolyte described in the present invention, which can further reduce the problem of the space charge layer between the sulfide electrolyte and the oxide positive electrode material.

[0056] Specifically, by pre-introducing a lithium-rich layer on the surface of the oxide positive electrode, the loss of lithium ions can be compensated, the lithium concentration gradient at the interface can be reduced, and thus the formation of a space charge layer can be suppressed; the interface impedance can be reduced, and the ion transfer efficiency can be improved. After the lithium-rich layer is pre-set, the lithium ion concentration on the positive electrode surface is increased, the energy barrier at the interface is reduced, and the lithium ion migration is smoother, thereby improving the rate performance and cycle stability of the all-solid-state battery; the high reactivity of the sulfide electrolyte to the oxide positive electrode may lead to interfacial decomposition (such as sulfide oxidation to generate SO X , Li2S, etc.), further exacerbating the space charge layer effect. The lithium-rich layer can act as a physical / chemical barrier to reduce the direct contact between the positive electrode and the electrolyte, inhibit the occurrence of side reactions, and maintain interface stability; the difference in mechanical properties between the oxide positive electrode (rigid) and the sulfide electrolyte (soft) may lead to poor interface contact. The lithium-rich layer (such as flexible lithium compounds) can fill the interfacial voids, enhance the interfacial contact, and relieve the volume change stress during the charge and discharge process; high-voltage oxide positive electrodes (such as high-nickel NCM, lithium-rich materials) are more likely to induce oxidative decomposition of sulfide electrolytes. The lithium-rich layer can adjust the potential distribution at the interface, delay the breakthrough of the electrochemical window of the electrolyte, and improve high-voltage compatibility.

[0057] Since it is used directly in the positive electrode active layer, the particle size of the solid electrolyte should match the requirements of the positive electrode active layer. Generally, the D of the doped sulfide solid electrolyte is 50 Particle size ≤1μm.

[0058] Preferably, based on the mass of the positive electrode active layer of the positive electrode sheet as 100%, the mass proportion of the doped sulfide solid electrolyte is 1% to 35%, for example, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 32% or 35%, etc.

[0059] Preferably, based on the mass of the positive electrode active layer of the positive electrode sheet being 100%, the mass proportion of the positive electrode active material is 70% to 90%, for example, 70%, 72%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, or 90%, etc.; the mass proportion of the conductive agent is 1% to 5%, for example, 1%, 2%, 3%, 4%, or 5%, etc. A binder may not be required in the positive electrode active layer of an all-solid-state battery.

[0060] Preferably, the positive electrode active material (oxide positive electrode) can be a ternary positive electrode material (NCM or NCA), a lithium-rich manganese-based material, lithium iron phosphate, lithium cobalt oxide, etc.

[0061] In a fourth aspect, the present invention provides a battery comprising the doped sulfide solid electrolyte described in the first aspect.

[0062] Of course, the doped sulfide solid electrolyte of the present invention can also be prepared into a solid electrolyte membrane with or without other solid electrolytes or binders, and assembled into a battery through the process of laminating the positive electrode sheet, solid electrolyte membrane and negative electrode sheet. 50 Particle size ≤15μm.

[0063] It should also be noted that due to space limitations and to avoid redundancy, the present invention does not exhaustively list all point values ​​within the above numerical range, but is not limited to the listed values. Other unlisted values ​​within the above numerical range are also applicable.

[0064] Compared with the existing technical solutions, the present invention has at least the following beneficial effects:

[0065] The present invention dopes a specific oxide of A into the basic component of the sulfide solid electrolyte, and utilizes the fact that the soft acid element A is more easily reacted with the soft base S. 2- It preferentially binds to replace P, forming an AS covalent bond with a higher polarity than PS, thereby improving the air stability of the sulfide solid electrolyte and effectively inhibiting its hydrolysis. Furthermore, the specific electronic configuration of the metal element A fully fills the valence electron layer, providing strong stability and effectively improving the antioxidant capacity of the sulfide solid electrolyte. Furthermore, A exhibits a lower valence state in the doped sulfide solid electrolyte, avoiding the effects of high-valence metal doping elements.

[0066] In the preparation method described in the present invention, the raw materials are pretreated with microwave plasma in advance. The surface oxides of the raw materials are reduced by the plasma. The microwave energy simultaneously causes lattice defects in the raw materials, thereby improving the subsequent reaction activity. Then, a mechanochemical vapor deposition synergistic reaction occurs during the grinding process to promote the synthesis of nanocrystals. Finally, in-situ densification hot pressing sintering is adopted to simultaneously achieve powder forming, sintering and densification, simplify the process flow, and ensure that the obtained doped sulfide solid electrolyte has excellent performance.

[0067] In the present invention, the positive electrode active material is pre-lithiated by using a lithium source to form a lithium-rich layer to obtain a pre-lithiated positive electrode active material, which is then mixed with the doped sulfide solid electrolyte described in the present invention. This can further reduce the problem of the space charge layer between the sulfide electrolyte and the oxide positive electrode material. DETAILED DESCRIPTION

[0068] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0069] It should be apparent to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.

[0070] Example 1

[0071] This embodiment provides a doped sulfide solid electrolyte, including a sulfide solid electrolyte basic component Li 10 PS 4.5 Cl3Br3, the sulfide solid electrolyte basic component contains dopant Yb2O3; the ratio of the molar amount of the metal element Yb to the molar amount of the sulfide solid electrolyte basic component is 0.08:1, and the chemical structural formula of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 .

[0072] The preparation method of the doped sulfide solid electrolyte comprises:

[0073] The raw materials LiCl, LiBr, P2S5, Li2S, and Yb2O3 were weighed in a molar ratio of 3:3:0.5:2:0.04 and placed in an Ar plasma atmosphere for microwave plasma pretreatment for 10 minutes to obtain a pretreated material; the pretreated material was poured into a zirconia grinding jar (with a diamond-like carbon coating on the inner wall) for grinding, and a mechanical chemical vapor deposition synergistic reaction occurred. The speed was controlled at 700 rpm, and a pulsed frequency conversion mode (start-stop ratio of 10:5) was added to promote the formation of nanocrystals. The grinding time was 10 hours to obtain a grinding material; finally, the grinding material was subjected to in-situ densification hot pressing sintering, using a gradient heating strategy to gradually increase the temperature and pressure over time, reaching 50 MPa at 200°C, 100 MPa at 300°C, and 300 MPa at 400°C. The hot pressing holding time for each stage was 4 hours to obtain a doped sulfide solid electrolyte; and then the sand mill was used to grind and crush it into D 50 Two samples with particle sizes of 600 nm and 3 μm were used;

[0074] Example 2

[0075] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the amount of the raw material Yb2O3 is adjusted to change the doping amount of the dopant Yb2O3 in the doped sulfide solid electrolyte. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Yb 0.22 Cl3Br3O 0.33 Except for the above, other conditions are exactly the same as those in Example 1.

[0076] Example 3

[0077] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the amount of the raw material Yb2O3 is adjusted to change the doping amount of the dopant Yb2O3 in the doped sulfide solid electrolyte. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Yb 0.16 Cl3Br3O 0.24 , except for the above, other conditions are exactly the same as those in Example 1.

[0078] Example 4

[0079] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the amount of the raw material Yb2O3 is adjusted to change the doping amount of the dopant Yb2O3 in the doped sulfide solid electrolyte. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Yb 0.04 Cl3Br3O 0.06 , except for the above, other conditions are exactly the same as those in Example 1.

[0080] Example 5

[0081] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the amount of the raw material Yb2O3 is adjusted to change the doping amount of the dopant Yb2O3 in the doped sulfide solid electrolyte. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Yb 0.01 Cl3Br3O 0.015 , except for the above, other conditions are exactly the same as those in Example 1.

[0082] Example 6

[0083] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the amount of the raw material Yb2O3 is adjusted to change the doping amount of the dopant Yb2O3 in the doped sulfide solid electrolyte. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Yb 0.004 Cl3Br3O 0.006 , except for the above, other conditions are exactly the same as those in Example 1.

[0084] Example 7

[0085] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the raw material is adjusted from Yb2O3 to twice the molar amount of MgO, so that the dopant in the doped sulfide solid electrolyte becomes MgO. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Mg 0.08 Cl3Br3O 0.08 , except for the above, other conditions are exactly the same as those in Example 1.

[0086] Example 8

[0087] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the raw material is adjusted from Yb2O3 to twice the molar amount of PdO, so that the dopant in the doped sulfide solid electrolyte becomes PdO. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Pd 0.08 Cl3Br3O 0.08 , except for the above, other conditions are exactly the same as those in Example 1.

[0088] Example 9

[0089] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the raw material is adjusted from Yb2O3 to twice the molar amount of ZnO, so that the dopant in the doped sulfide solid electrolyte becomes ZnO. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Zn 0.08 Cl3Br3O 0.08 , except for the above, other conditions are exactly the same as those in Example 1.

[0090] Example 10

[0091] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the raw material is adjusted from Yb2O3 to twice the molar amount of BaO, so that the dopant in the doped sulfide solid electrolyte becomes BaO. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Ba 0.08 Cl3Br3O 0.08 , except for the above, other conditions are exactly the same as those in Example 1.

[0092] Example 11

[0093] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the raw material is adjusted from Yb2O3 to twice the molar amount of SrO, so that the dopant in the doped sulfide solid electrolyte becomes SrO. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Sr 0.08 Cl3Br3O 0.08 , except for the above, other conditions are exactly the same as those in Example 1.

[0094] Example 12

[0095] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the raw material is adjusted from Yb2O3 to twice the molar amount of CaO, so that the dopant in the doped sulfide solid electrolyte becomes CaO. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Ca 0.08 Cl3Br3O 0.08 , except for the above, other conditions are exactly the same as those in Example 1.

[0096] Example 13

[0097] This embodiment provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the raw material is adjusted from Yb2O3 to twice the molar amount of BeO, so that the dopant in the doped sulfide solid electrolyte becomes BeO. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Be 0.08 Cl3Br3O 0.08 , except for the above, other conditions are exactly the same as those in Example 1.

[0098] Comparative Example 1

[0099] This comparative example uses the sulfide solid electrolyte basic component Li in Example 1. 10 PS 4.5 Cl3Br3 for subsequent testing.

[0100] Comparative Example 2

[0101] This comparative example provides a doped sulfide solid electrolyte. In the preparation method of the doped sulfide solid electrolyte, the raw material is adjusted from Yb2O3 to twice the molar amount of ZrO2, so that the dopant in the doped sulfide solid electrolyte becomes ZrO2. The chemical structure of the doped sulfide solid electrolyte is Li 10 PS 4.5 Yb 0.08 Cl3Br3O 0.12 Adjusted to Li 10 PS 4.5 Zr 0.08 Cl3Br3O 0.16 , except for the above, other conditions are exactly the same as those in Example 1.

[0102] Application Example 1

[0103] The present invention provides an all-solid-state battery, comprising the doped sulfide solid electrolyte provided in any one of Examples 1 to 13 or Comparative Example 2, or the sulfide solid electrolyte basic component of Comparative Example 1. The manufacturing and assembly method of the all-solid-state battery comprises:

[0104] Preparation of positive electrode mixed powder: nickel cobalt lithium manganese oxide ternary material LiNi 0.9 Co 0.1 Mn 0.1O2 and lithium source AlHLiO2 were mixed in a mass ratio of 99:0.5 and ground for 1 hour at a grinding speed of 400 rpm, and then calcined at 450 ° C for 2 hours to obtain a calcined material; the calcined material was then mixed with D 50 The doped sulfide solid electrolyte or sulfide solid electrolyte basic component with a particle size of 600 nm is mixed in a mass ratio of 8:2, and ground and mixed at 400 rpm for 30 minutes to obtain a pre-lithiated positive electrode active material;

[0105] In a glove box, the pre-lithiated cathode active material and the conductive agent VGCF (the conductive agent accounts for 3% of the total mass) are placed in a grinding jar, and 5mm diameter zirconia balls are added, with a ball-to-material ratio of 5:1. After stirring evenly, the screws are tightened and the cover interface is sealed with tape. The grinder speed is set to 350rpm, and the forward rotation is 8 minutes, the rest is 2 minutes, and the reverse rotation is 8 minutes, for a total of 38 minutes. The above grinding jar is placed symmetrically, and the fixing knob is tightened and then grinding is started to obtain a positive electrode mixed powder.

[0106] Prepare the solid electrolyte layer: Prepare the solid electrolyte layer using the same doped sulfide solid electrolyte or sulfide solid electrolyte base components as those used in the positive electrode mixture. Place 100-120 mg of the electrolyte into an alumina ceramic mold (10 mm diameter) and press it into a solid electrolyte sheet using a press (pressure parameters: 100-130 MPa, 30 seconds to 2 minutes). Remove excess solid electrolyte powder with an ear bulb.

[0107] Assemble the battery: Weigh 25 mg of the positive electrode mixture powder and spread it flat on the solid electrolyte sheet. Rotate the stainless steel electrode indenter to the bottom of the mold and rotate the indenter to flatten the powder. Remove the indenter and place a piece of carbon-coated aluminum foil (10 mm) on top of the powder. Use a press to maintain the pressure at 400 MPa for 2 minutes and use an ear bulb to remove excess positive electrode mixture powder. Then weigh it a second time to calculate the actual solid electrolyte loading. Place an indium sheet and a copper-lithium composite tape on the other side of the solid electrolyte sheet in sequence, with indium facing the middle electrolyte layer and lithium facing indium, with a diameter of 10 mm. Finally, fasten the mold and indenter and tighten the nut to obtain an all-solid-state mold battery.

[0108] Application Example 2

[0109] The present invention provides an all-solid-state battery, comprising the doped sulfide solid electrolyte provided in Example 1. In the manufacturing and assembly method of the all-solid-state battery, when preparing the positive electrode mixed powder, the lithium source is not used, and the nickel cobalt manganese oxide ternary material is directly mixed with the doped sulfide solid electrolyte.

[0110] Except for the above, other conditions are exactly the same as those in Application Example 1.

[0111] Application control group 1

[0112] The positive electrode mixed powder of the control group of this application does not contain the doped sulfide solid electrolyte or the basic component of the sulfide solid electrolyte. The doped sulfide solid electrolyte of Example 1 is used in the solid electrolyte layer. Except for the above, other conditions are exactly the same as those of Application Example 1.

[0113] Characterization and testing:

[0114] Ⅰ. The solid electrolytes obtained in Examples 1 to 13 and Comparative Examples 1 and 2 were tested as follows:

[0115] (1) Air stability test:

[0116] A1. Turn on the dehumidifier and wait for the environment to stabilize below -45°C for at least half an hour.

[0117] A2. Electrolyte Exposure: Lay the dried weighing paper flat on the test bench and press the four corners with heavy objects to prevent the weighing paper from blowing away. Take 0.5±0.03g of electrolyte and spread it flat on the weighing paper. Use a medicine spoon to spread it to a thickness of 1±0.3mm. Let it stand for 4.5 hours before collecting the material.

[0118] A3. Weigh 120-130 mg of solid electrolyte powder and place it in a mold (10 mm diameter). Press it into an electrolyte sheet using a press (parameter: 400 MPa). Place stainless steel blocking electrodes at both ends of the electrolyte sheet.

[0119] A4. Use an electrochemical workstation to measure the sample impedance using electrochemical impedance spectroscopy to obtain the resistance value R (Ω) of the solid electrolyte. The test frequency is 0.01 MHz to 1 MHz, the test disturbance voltage is 15 mV, and the test temperature is the temperature inside the glove box.

[0120] A5. Take out the electrolyte sheet and use a micrometer to measure the thickness L (cm) of the solid electrolyte.

[0121] A6. Then calculate the ionic conductivity σ of the solid electrolyte at the temperature inside the glove box using the formula σ=L / (R·S); where: σ—ionic conductivity of the solid electrolyte (S·cm -1 ); L—thickness of solid electrolyte (cm); R—intrinsic resistance of solid electrolyte (Ω); S—cross-sectional area of ​​solid electrolyte (cm 2 );

[0122] A7. Test the conductivity of the solid electrolyte before and after exposure according to steps A3 to A6. Calculate the air stability of the solid electrolyte using the formula: Air stability = conductivity before exposure / conductivity after exposure × 100%.

[0123] (2) Antioxidant capacity electrochemical window test:

[0124] B1. Weigh 100 mg of the total material according to the mass ratio of conductive agent VGCF: sulfide solid electrolyte = 20:80, place it in a mortar and grind it by hand for 10 minutes, and mix it evenly to obtain a mixture;

[0125] B2. Weigh 100 mg of sulfide solid electrolyte powder and place it into a mold liner (10 mm diameter). Press it into an electrolyte sheet using a press (parameter: 400 MPa).

[0126] B3. Place 25 mg of the mixture from step (1) on one end of the electrolyte sheet, flatten it with a mold, and compact it with a press (parameter: 400 MPa); introduce a Li sheet at the other end; perform LSV testing using an electrochemical workstation, set the open circuit voltage to ~6 V, and the scan rate to 0.1 mV / s to obtain the oxidation window (unit: V).

[0127] II. The following tests were performed on the batteries obtained from Use Case 1 and Control Group 1:

[0128] (1) 0.1C first coulombic efficiency: At 35±3℃, charge at a constant current of 0.1C to 3.7V, and charge at a constant voltage of 3.7V to a cutoff current of 0.05C to obtain the first cycle 0.1C charging capacity A1; then discharge at a constant current of 0.1C to 2.0V to obtain the first cycle 0.1C discharge capacity A2; first efficiency = A2 / A1·100%.

[0129] (2) 0.1C / 0.5C discharge capacity test: At 35±3℃, charge at a constant current of 0.1C / 0.5C to 3.7V, and charge at a constant voltage of 3.7V to a cutoff current of 0.05C; then discharge at a constant current of 0.1C / 0.5C to 2.0V, and obtain a discharge capacity of 0.1C / 0.5C.

[0130] (3) Test method for 0.5C / 0.5C capacity retention rate: At 35±3℃, charge the battery to 3.7V at 0.5C constant current, charge at 3.7V constant voltage to a cutoff current of 0.05C, and discharge the battery to 2.0V at 0.5C constant current. The first discharge capacity of 0.5C is recorded as D1. Repeat the charge and discharge steps for N cycles, and the Nth cycle discharge capacity is recorded as DN. The capacity retention rate of the Nth cycle is calculated based on the first cycle discharge capacity and the Nth cycle discharge capacity. The capacity retention rate of the Nth cycle = (DN / D1) × 100%.

[0131] The above test results are shown in Table 1.

[0132] Table 1

[0133]

[0134] As can be seen from Table 1:

[0135] Comparing Examples 1 to 6, the excessive doping level of Metal Element A in Example 2 improves air stability, but the excessive addition of Metal Element A leads to excessively high electronic conductivity in the electrolyte. This high electronic conductivity can lead to the formation of electron conduction paths within the electrolyte, triggering battery self-discharge and, in turn, reducing capacity retention. Furthermore, electrons directly participate in side reactions (such as electrolyte reduction), consuming active lithium ions and reducing charge-discharge efficiency. High electronic conductivity exacerbates redox reactions between the electrolyte and the electrode (such as the high-voltage positive electrode), forming an interfacial decomposition layer (such as Li2S), increasing interfacial impedance. Excessive electronic conductivity can also severely compromise the battery's electrochemical stability and cycle life. However, a low doping level of Metal Element A, as in Example 6, is insufficient to achieve an optimal effect, resulting in significant performance differences. Comparing Example 1 with Examples 7 to 13, other Metal Element A, except Yb, also play a role in improving air stability at appropriate doping levels, with Yb being the most effective. Comparing Example 1 with Comparative Examples 1 and 2 reveals that the air stability and cycle performance of the batteries without Metal Element A doping or with high-valent metal elements are inferior.

[0136] Comparing the battery containing the sulfide solid electrolyte of Example 1 in Application Example 1 with Application Example 2, it can be found that the formation of a lithium-rich layer on the positive electrode active material can effectively improve the problem of the space charge layer between the sulfide electrolyte and the oxide positive electrode material, thereby effectively improving the battery performance.

[0137] From the above, it can be seen that the present invention dopes a specific oxide of A into the basic component of the sulfide solid electrolyte, utilizing the fact that the soft acid element A is more easily reacted with the soft base S 2- It preferentially combines to replace P, forming an AS covalent bond with a higher polarity than PS, thereby improving the air stability of the sulfide solid electrolyte and effectively inhibiting the hydrolysis of the sulfide electrolyte; at the same time, the valence electron layer in the specific electronic configuration structure of the metal element A is fully filled, and the stability is strong, which can effectively improve the antioxidant capacity of the sulfide solid electrolyte. In addition, A presents a lower valence state in the doped sulfide solid electrolyte, avoiding the influence of high-valence metal doping elements. The present invention further uses a lithium source to pre-lithiate the positive electrode active material to form a lithium-rich layer, obtains the pre-lithiated positive electrode active material, and then mixes it with the doped sulfide solid electrolyte described in the present invention, which can further reduce the problem of the space charge layer between the sulfide electrolyte and the oxide positive electrode material.

[0138] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the scope of protection of the present invention.

[0139] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any appropriate manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0140] In addition, the various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A doped sulfide solid electrolyte, characterized in that: It includes a sulfide solid electrolyte basic component, the sulfide solid electrolyte basic component contains a dopant, and the dopant includes an oxide of a metal element A; the atomic valence electron layer of the metal element A is fully filled, and A is a soft acid element; in the doped sulfide solid electrolyte, the valence state of A does not exceed +3.

2. The doped sulfide solid electrolyte according to claim 1, characterized in that: The doped sulfide solid electrolyte satisfies at least one of the following conditions: 1) The basic components of the sulfide solid electrolyte include at least one of a Thio-LISICON series electrolyte, an Argyrodite series electrolyte, or a glass ceramic electrolyte; 2) The metal element A includes at least one of Be, Mg, Ca, Sr, Ba, Zn, Pd, Yb or No; 3) The ratio of the molar amount of the metal element A to the molar amount of the basic component of the sulfide solid electrolyte is (0.01-0.2):1; 4) The chemical structure of the doped sulfide solid electrolyte includes Li a P b S c A e X d O f , wherein X comprises at least one of Cl, I, Br or F; a=2.5-12, b=0.5-2.5, c=4-15, d=0.5-3.5, e=0.0067-0.2, f=0.01-0.3; and e:f=1:(1-1.5), or f=e, or 2f=3e; 5) D of the doped sulfide solid electrolyte 50 Particle size ≤15μm.

3. A method for preparing the doped sulfide solid electrolyte according to claim 1 or 2, characterized in that: The preparation method comprises: The sulfide solid electrolyte basic component raw material and the dopant raw material are mixed, and subjected to microwave plasma pretreatment to generate a reduction reaction to obtain a pretreated material; Grinding the pretreated material to generate a mechanical chemical vapor deposition synergistic reaction to generate nanocrystals to obtain a grinding material; The ground material is subjected to in-situ densification and hot pressing sintering to obtain the doped sulfide solid electrolyte.

4. The method for preparing a doped sulfide solid electrolyte according to claim 3, wherein: The dopant raw material includes an oxide of metal element A.

5. The method for preparing a doped sulfide solid electrolyte according to claim 3, wherein: The microwave plasma pretreatment is carried out in an inert plasma atmosphere; the inert atmosphere comprises Ar; And / or, the microwave plasma pretreatment has a power range of 100-300 W, a vacuum degree of 0.01-0.1 Pa, a temperature of 20-65° C., and a time of 5-20 min.

6. The method for preparing a doped sulfide solid electrolyte according to claim 3, wherein: The grinding comprises at least one of ball milling, high energy vibration milling, air flow milling, ultrasonic assisted grinding or cryo-grinding; The ball milling is carried out in a zirconia ball mill jar, the inner wall of which is coated with a diamond-like carbon coating; and / or the rotation speed of the ball mill is 400-700 rpm, and a pulse frequency conversion mode is adopted with a start-stop ratio of 10:(5-2); and / or the ball milling time is 30 min-12 h.

7. The method for preparing a doped sulfide solid electrolyte according to claim 3, wherein: The temperature and pressure of the in-situ densification hot pressing sintering are increased step by step; And / or, the temperature range of the in-situ densification hot pressing sintering is 50-500° C., the pressure range is 5-300 MPa, and the processing time of each stage is 30 min-12 h.

8. A positive electrode sheet, characterized in that: The positive electrode sheet contains the doped sulfide solid electrolyte according to claim 1 or 2.

9. The positive electrode sheet according to claim 8, characterized in that: The positive electrode sheet satisfies at least one of the following conditions: 1) The positive electrode active layer of the positive electrode sheet contains the doped sulfide solid electrolyte; 2) The positive electrode active material in the positive electrode active layer of the positive electrode sheet is pre-lithiated to form a lithium-rich layer on the surface; and / or, the lithium-rich layer comprises at least one of Li2CO3, Li3N, Li2O, Li2TiO3, Li3PO4, AlF6Li3, AlHLiO2, AlCl4Li or Li2O3Ti; and / or, the mass of the lithium-rich layer accounts for 0.1% to 1% of the mass of the positive electrode active material; 3) Based on the mass of the positive electrode active layer of the positive electrode sheet being 100%, the mass of the doped sulfide solid electrolyte accounts for 1% to 35%, the mass of the positive electrode active material accounts for 70% to 90%, and the mass of the conductive agent accounts for 1% to 5%; 4) In the positive electrode active layer of the positive electrode sheet, the positive electrode active material includes at least one of nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium-rich manganese base, lithium iron phosphate or lithium cobalt oxide.

10. A battery, characterized in that: Contains the doped sulfide solid electrolyte according to claim 1 or 2 or contains the positive electrode sheet according to claim 8 or 9.

Citation Information

Patent Citations

  • Sulfide solid electrolyte and preparation and application thereof

    CN114361580A

  • Preparation and application of group IIA element and double halogen doped sulfide solid electrolyte

    CN114649562A

  • Preparation method and application of lithium argyrodite type solid electrolyte and sulfide film

    CN117457972A

  • Preparation method of lithium sulfide nano-particles, lithium sulfide nano-particles and application of lithium sulfide nano-particles

    CN117566692A

  • Sulfide solid electrolyte, preparation method thereof and all-solid-state battery

    CN120511348A

Cited By

  • Sulfide solid electrolyte, acoustic resonance synthesis method thereof and all-solid-state battery

    CN121192242A